Developmental tasks and well-being in adolescent elite athletes in comparison with recreational/non-athletes - Ohlert, J.; Ott, I. (European Journal of Sport Science, 2017)
Young elite athletes (EA) have to solve the same developmental tasks (DTs) as non-athletes, even though they spend a lot of time with their sports and have to solve certain sports-related DTs in addition [Ohlert & Kleinert (2014). Entwicklungsaufgaben jugendlicher Elite-Handballerinnen und -Handballer [Developmental tasks in adolescent elite handball players]. Zeitschrift für Sportpsychologie, 21(4), 161-172. doi:10.1026/1612-5010/a000129]. The aim of this study was to find out if this situation leads to a shortfall in certain DTs and, furthermore, to a reduced well-being in adolescent EA. In total, 185 EA participated in the survey together with 166 recreational/non-athletes (RA). Participants were between 16 and 19 years old (69% female) and answered questions regarding the relevance of different DTs, their actual progression, satisfaction with their actual progression, and the WHO-5 measure for well-being. Compared to the RA group, the EA group reported a different relevance for some DTs. No significant differences were found between the two groups in progression or satisfaction with progression. The stepwise multiple regression resulted in two significant predictors for well-being in EA: satisfaction with progression in the DTs "to find oneself" and "circle of friends". For RA, the analysis revealed only satisfaction with progression in "circle of friends" as a significant predictor. Implications are that, at least for this age group, problems with DTs were not detected for the adolescent EA. However, if satisfaction with the own progression in certain DTs is low, well-being will also be reduced.